2020
DOI: 10.1155/2020/6642568
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Iron Deficiency Anemia Are Common Epidemiological Conditions in Saudi Arabia: Report of the National Epidemiological Survey

Abstract: Iron deficiency is the most prevalent nutritional deficiency worldwide. According to an estimate by the World Health Organization, up to 27% of the world’s population experience iron deficiency anemia (IDA). Studies conducted in the Middle East, including Saudi Arabia, have suggested that IDA is the most common cause of anemia, especially among females. This study aimed to determine the prevalence of IDA and iron deficiency (ID) among apparently healthy young university students from four regions in Saudi Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
3
15
1
Order By: Relevance
“…Our findings indicate that approximately one-third of Saudi adults exhibit iron deficiency (23.2%), consistent with that reported in the literature [ 38 ], but higher than the global estimates [ 4 , 38 ]. Hwalla et al [ 15 ] reported that in the Middle East the second highest prevalence of anemia in women of childbearing age was found in Saudi Arabia (40%), followed by Egypt (47.2%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings indicate that approximately one-third of Saudi adults exhibit iron deficiency (23.2%), consistent with that reported in the literature [ 38 ], but higher than the global estimates [ 4 , 38 ]. Hwalla et al [ 15 ] reported that in the Middle East the second highest prevalence of anemia in women of childbearing age was found in Saudi Arabia (40%), followed by Egypt (47.2%).…”
Section: Discussionsupporting
confidence: 92%
“…In our findings, iron deficiency significantly differed based on age and sex, with women exhibiting a higher prevalence of iron deficiency than men (41.2% vs. 10.9%, respectively). This result was observed nationally [ 38 ], regionally [ 15 ], and internationally [ 4 ]. Furthermore, age differences exist in iron deficiency prevalence, particularly demonstrating a higher prevalence in young than in older adults; this is consistent with the results of other studies [ 4 , 15 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 72%
“…As previously stated, iron deficiency anemia is the most common hematological problem, particularly among women during their reproductive years, and it is a global issue [23][24][25]. Many studies have centered on the prevalence of anemia among Saudi females [26,27]. The present study aims to support an alternative natural nutritional source, namely raisins, to treat iron deficiency anemia induced in the rat model by repeated chronic bleeding.…”
Section: Discussionmentioning
confidence: 94%
“…After searching and conducting a critical appraisal of the articles, 14 studies were selected for the systematic review [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. A summary of these studies is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%